A detailed study on heat of reaction and heat rate determination of nitrobenzene hydrogenation to aniline reaction using power compensation reaction calorimeter - Kumar, Rajendra; Mane, Pradip R.; Shingote, Savita K.; Mali, Nilesh A. (Process Safety Progress, 2025)
The present study reports experimental heat of reaction and heat rate data of nitrobenzene hydrogenation to aniline reaction with process parameter variation. A high-pressure isothermal power compensation reaction calorimeter was used for this work. A systematic and step-by-step procedure is also reported to determine the heat of reaction and heat rate for a highly exothermic reaction. The sensitivity of experimental molar heat of reaction (kJ/mol) and evolved heat rate (W) values for nitrobenzene hydrogenation reaction was analyzed for various important process parameters, such as temperature, pressure, substrate quantity, solvent quantity, catalyst quantity, RPM, and hydrogen feed rate. Nitrobenzene hydrogenation reactions were conducted using ethanol as solvent and 5% Pd/C as a catalyst with 55-65 degrees C temperature and 7-9 Bar absolute pressure range. More than 99.99% conversion of nitrobenzene to aniline was obtained, and no other by-products were found. The average experimental nitrobenzene hydrogenation heat of reaction of 21 different experiments was found to be -581.87 kJ/mol, and the maximum heat rate during the nitrobenzene hydrogenation reaction was found to be 16.16 W for experiments using 10 gm of nitrobenzene in solvent.
Keywords: heat of reaction; heat rate; Hydrogenation; nitrobenzene; power compensation; reaction calorimeter